Synthesis of 3-substituted quinolin-2(1H)-ones via the cyclization of o-alkynylisocyanobenzenes - Ailada Charoenpol (2019)
© The Royal Society of Chemistry. A facile synthesis of various functionalized 3-substituted quinolin-2(1H)-ones through Ag(i) nitrate-catalyzed cyclization of o-alkynylisocyanobenzenes is described. The reaction allows rapid and convenient access to 3-substituted quinolin-2(1H)-one scaffolds in moderate to good yields.